Análisis confirmatorio y coeficiente Omega como propiedades psicométricas del instrumento Clima Laboral de Sonia Palma - Salazar Vargas, Carlos (2017)
The objective of this work is to know the approximation of the psychometric properties of the Organizational Climate scale. The scale was administered to 391 workers from different areas of a university higher education institution of Metropolitan Lima, whose ages ranged from 18 to 48 years. The results reveal an internal consistency through the omega coefficient (ω = 0.94) considered as good; Likewise, the dimensions register reliability with omega values from 0.73 to o.83. Within the Construct Validity process, confirmatory factor analysis indicated that with four factors, one less than the initial publication, underlying the construct, the structural model was confirmed with adjustments of the indicators such as MRM, GFI, TLI, IFC and RMSEA, and as a contrast indicator of the model with higher adjustment the AIC.